2013
DOI: 10.1111/jnc.12379
|View full text |Cite
|
Sign up to set email alerts
|

Galanin stimulates neurite outgrowth from sensory neurons by inhibition of Cdc42 and Rho GTPases and activation of cofilin

Abstract: We and others have previously shown that the neuropeptide galanin modulates neurite outgrowth from adult sensory neurons via activation of the second galanin receptor; however, the intracellular signalling pathways that mediate this neuritogenic effect have yet to be elucidated. Here, we demonstrate that galanin decreases the activation state in adult sensory neurons and PC12 cells of Rho and Cdc42 GTPases, both known regulators of filopodial and growth cone motility. Consistent with this, activated levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 69 publications
(189 reference statements)
2
21
0
Order By: Relevance
“…Galanin is involved in diverse physiological functions, including nociception, arousal/sleep regulation, cognition, and many aspects of neuroendocrine activities that are associated with feeding, energy metabolism, thermoregulation, osmotic and water balance, and reproduction (Mechenthaler, 2008). A recent publication by Hobson and colleagues using differentiated PC12 cells suggests a role of galanin in neurite outgrowth (Hobson et al, 2013). We observed a high abundance of galanin/pepcan colocalization in the cell bodies of the LC, as well as in many of the axonal projections, throughout the brain and those descending to the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Galanin is involved in diverse physiological functions, including nociception, arousal/sleep regulation, cognition, and many aspects of neuroendocrine activities that are associated with feeding, energy metabolism, thermoregulation, osmotic and water balance, and reproduction (Mechenthaler, 2008). A recent publication by Hobson and colleagues using differentiated PC12 cells suggests a role of galanin in neurite outgrowth (Hobson et al, 2013). We observed a high abundance of galanin/pepcan colocalization in the cell bodies of the LC, as well as in many of the axonal projections, throughout the brain and those descending to the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…GAL 2 predominantly couples to a G q/11 -type G protein, leading to phospholipase C activation, which stimulates Ca 2+ release via inositol phosphate hydrolysis and opens Ca 2+ -dependent ion channels in a PTXresistant manner, in both GAL 2 -transfected cell lines (Smith et al, 1997b;Borowsky et al, 1998;Fathi et al, 1998;Pang et al, 1998;Wang et al, 1998c) and GAL 2 -expressing rat microglial cells (Ifuku et al, 2011). GAL 2 activation led to a decrease in both Rho and Cdc42 GTPase activity and activation of cofilin in rat PC12 pheochromocytoma cells (Hobson et al, 2013). In SCLC cells, another signaling pathway has been proposed for GAL 2 involving functional coupling to a G 12/13 -type G protein and subsequent activation of the small GTPase protein Rho A (Wittau et al, 2000).…”
Section: B Galanin Receptor Signalingmentioning
confidence: 99%
“…An early study reported that treatment with galanin failed to induce neurite outgrowth in PC12 cells (Klimaschewski et al, 1995), whereas a more recent study demonstrated that galanin significantly increased the percentage of PC12 cells Galanin Family Peptides and Receptors exhibiting neurite outgrowth (Hawes et al, 2006;Hobson et al, 2013).…”
Section: Regeneration and Neurite Outgrowthmentioning
confidence: 99%
See 1 more Smart Citation
“…This can lead to downstream PI3K-dependent phosphorylation of protein kinase B that results in the inhibition of caspase 3 and caspase 9 activity [34,73,74]. Activation of the G q protein coupled GalR2 receptor has been shown to stimulate the Rho family of GTPases [75]. GalR2 activates both the G 12 protein and signals through the G 12 /Rho pathway and subsequently activates the small GTPase protein Rho A in small cell lung cancer cells [34,76].…”
Section: Galanin Receptor Subtypementioning
confidence: 99%